The diagnostic value of the ocular tilt reaction plus head tilt subjective visual vertical (±45°) in patients with acute central vascular vertigo - Feng, Yufei; Zhao, Tongtong; Wu, Yuexia; Ling, Xia; Zhang, Menglu; Song, Ning; Kim, Ji-Soo; Yang, Xu (Frontiers in Neurology, 2022)
Objectives To investigate the localization diagnostic value of the ocular tilt reaction (OTR) plus head tilt subjective visual vertical (SVV) in patients with acute central vascular vertigo (ACVV). Methods We enrolled 40 patients with acute infarction, 20 with unilateral brainstem infarction (BI) and 20 with unilateral cerebellar infarction (CI). We also included 20 patients with unilateral peripheral vestibular disorders (UPVD) as the control group. The participants completed the OTR and SVV during head tilt (±45°) within 1 week of symptom onset. Results In patients with ACVV, including that caused by lateral medullary infarction (100%, 2/2), partial pontine infarction (21%, 3/14), and cerebellum infarction (35%, 7/20), we observed ipsiversive OTR, similar to that seen in UPVD patients (80.0%, 16/20). Some of the patients with medial medullary infarction (50%, 1/2), partial pons infarction (42%, 6/14), midbrain infarction (100%, 2/2), and partial cerebellum infarction (30.0%, 6/20) showed contraversive OTR. The skew deviation (SD) of the BI group with ACVV was significantly greater than that of the UPVD group (6.60 ± 2.70° vs. 1.80 ± 1.30°, Z = −2.50, P = 0.012), such that the mean SD of the patients with a pons infarction was 9.50° and that of patients with medulla infarction was 5.00°. In ACVV patients with no cerebellar damage, the area under the curve of the receiver operating characteristic curve corresponding to the use of SD to predict brainstem damage was 0.92 (95%CI: 0.73–1.00), with a sensitivity of 100% and a specificity of 80% when SD ≥ 3°. We found no statistical difference in SD between the UPVD and CI groups (1.33 ± 0.58° vs. 1.80 ± 1.30°, Z = −0.344, P = 0.73). Compared with the UPVD patients, the ACVV patients with a partial pons infarction (43%, 6/14, χ2 = 13.68, P = 0.002) or medulla infarction (25%, 1/4, χ2 = 4.94, P = 0.103) exhibited signs of the ipsiversive E-effect with the contraversive A-effect, while those with a partial medulla infarction (50%, 2/4), pons infarction (43%, 6/14), or cerebellar infarction (60%, 12/20) exhibited a pathological symmetrical increase in the E-effect. Conclusions The evaluation of OTR plus head tilt SVV (±45°) in vertigo patients is helpful for identifying and diagnosing ACVV, especially when SD is ≥ 3° or the E-effect is symmetrically increased.